A Structural Model of Peak-Period Congestion: A Traffic Bottleneck with Elastic Demand - Arnott, Richard; de Palma, André; Lindsey, Robin (American Economic Review, 1993)
This paper considers the modeling of road congestion subject to peak-load demand. The standard model contains ambiguities and is poorly specified. These problems can be eliminated by working with a structural model that explicitly treats the congestion technology and drivers' behavioral decisions. The paper provides a detailed analysis of a particular structural model–William Vickrey's model of bottleneck congestion in the morning rush-hour auto commute, extended to treat elastic (i.e., price-sensitive) demand–and examines some economic implications of the structural approach.